SOCIAL MEDIA RESEARCH ON "LAMINATE VENEER": DURING COVID 19-PANDEMIC - Demirekin, Zeynep Basagaoglu; Buyukcavus, Esra (International Journal of Research -GRANTHAALAYAH, 2023)
Aim: The difficulty of asking questions to each other during the appointment process with their doctor, the long waiting times of the patients in the waiting rooms in the clinics, and the fact that it is easier to get medical information on the internet due to the ongoing COVID-19 virus infection. Porcelain laminate veneers (PLVs) have been frequently used to restore anterior teeth for nearly three decades, thanks to their aesthetic appeal, durability, and biocompatibility. Methodology: YouTube™ was searched by a researcher of this study using the keyword 'laminate veneer' on April 17, 2021. The most frequently used terms in this regard are 'laminate veneer' and 'laminate veneer restoration'. Analyzes were made on the Instagram application, along with YouTube. Results: Thirty-three videos were determined on YouTube™ on the topic of laminate veneer. The mean number of views was 46277.84 ± 128674.71, with the minimum view as ten and the maximum as 682478. The videos had a mean duration of 5:48 ± 4:64 with a range of 0:24–14:55. The mean number of "likes" for each video was 198 ± 424, and the mean number of "dislikes" was 17 ± 48. The most-liked video received 1700 "likes." The most-disliked video received 236"dislikes." The mean number of comments was 13.65 ± 31.58. The interaction rate was 1.67 ± 5.18, and the viewing rate was 2939.11 ± 6076.75 Conclusion: YouTube™ and Instagram still cannot be accepted as a completely confident resources of knowledge for patients who want to learn about oral aesthetic rehabilitation treatment with laminate veneers